Perancangan Sistem Autentikasi Pengguna dan Monitoring Kelistrikan CNC Router G-Weike WK1212 Berbasis Internet of Thing (IoT) - Suprijono, Herwin; Rahadian, Helmy; Islahudin, Nur (Universitas Semarang, 2023)
Internet of Thing (IoT) technology is able to manage devices to collect and exchange data over the internet network. IoT is one of the keys to implementing Industry 4.0 in various sectors such as manufacturing, transportation and even education. IoT can be utilized for laboratory device management. The Production Systems Laboratory, Faculty of Engineering, Dian Nuswantoro University has CNC-based machines such as a CNC router machine with the G-Eike brand type WK1212. Through the implementation of IoT, user data, operational time, and electricity such as voltage and current while the CNC machine is operating can be sent and stored on a database server. Furthermore, analysis of the data is carried out for various purposes such as predicting machine maintenance schedules. The results of the research that has been carried out regarding the design of user authentication systems and electrical monitoring of the CNC machine have been tested with good results in extracting the required data via IoT to then be used in predicting machine maintenance. It is known from the test results that the user (student) authentication system can be carried out by inputting a username and password based on student data registered by the laboratory assistant. Electrical data (voltage, current, power, energy, frequency and power factor) is successfully sent from the control panel periodically every 10 seconds to the broker. The broker managed to save the data received into the MySQL database. Keywords: Internet of Thing, CNC Router, G-Weike WK1212, Autentikasi, Monitoring. ABSTRAK Teknologi Internet of Thing (IoT) mampu mengelola perangkat untuk mengumpulkan serta bertukar data melalui jaringan internet. IoT menjadi salah satu kunci dalam penerapan industri 4.0 di berbagai sektor seperti manufaktur, transportasi, dan bahkan pendidikan. IoT dapat dimanfaatkan untuk manajemen perangkat laboratorium. Laboratorium Sistem Produksi Fakultas Teknik Universitas Dian Nuswantoro memiliki mesin-mesin berbasis CNC seperti mesin CNC router dengan Merk G-Eike tipe WK1212. Melalui penerapan IoT maka data pengguna, waktu operasional, dan kelistrikan seperti tegangan dan arus selama mesin CNC beroperasi dapat dikirim dan disimpan pada server basis data. Selanjutnya, analisis terhadap data tersebut dilakukan untuk berbagai keperluan seperti memprediksikan jadwal pemeliharaan mesin. Hasil dari penelitian yang telah dilakukan terkait perancangan sistem autentikasi pengguna dan monitoring kelistrikan mesin CNC tersebut telah diuji dengan hasil yang baik dalam menarik data-data yang dibutuhkan melalui IoT untuk kemudian dapat dimanfaatkan dalam prediksi pemeliharaan mesin. Diketahui dari hasil uji tersebut sistem autentikasi pengguna (mahasiswa) mampu dilakukan melalui input username dan password berdasarkan data mahasiswa yang didaftarkan oleh asisten laboratorium. Data kelistrikan (tegangan, arus, power, energi, frekuensi dan power factor) berhasil dikirim dari kontrol panel secara periodik tiap 10 detik ke broker. Broker berhasil menyimpan data yang diterima ke dalam database MySQL.